2017
DOI: 10.1080/03054985.2017.1305047
|View full text |Cite
|
Sign up to set email alerts
|

Left to their own devices: the everyday realities of one-to-one classrooms

Abstract: The past decade has seen the expansion of personal digital technologies into schools. With many students and teachers now possessing smartphones, tablets and laptops, schools are initiating 'one-to-one' and 'Bring Your Own Device' (BYOD) policies aiming to make use of these 'personal devices' in classrooms. While often discussed in terms of possible educational benefits and/or organizational risks, the actual presence of personal devices in schools tends to be more mundane in nature and effect. Drawing upon et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 12 publications
0
35
1
15
Order By: Relevance
“…The vulnerability of teaching can be understood not only from a personal psychological perspective when the pressure becomes emotionally too much, but also in terms of structural conditions of the teaching profession (Kelchtermans, 1993(Kelchtermans, , 2009)-being exposed and held accountable. Digitalisation has added further layers of complexity to teaching and learning (Mishra & Koehler, 2006;Orlando, 2013;Selwyn, Nemorin, Bulfin, & Johnson, 2017) in that it changes the circumstances and processes of teaching and learning as well as the roles, expectations, power, and values in educational contexts (Fransson, 2016). Although digital technologies can contribute added pedagogical value (George & Sanders, 2017;Haelermans, 2017), teachers may lack systematic strategies supporting students (Blikstad-Balas & Davies, 2017; and technologies may also result in teachers feeling pressurised to use them, even though this may be at odds with their own knowledge, practical skills, emotions, doubts about their potential, or their preferred ways of teaching (Convery, 2009;Howard, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of teaching can be understood not only from a personal psychological perspective when the pressure becomes emotionally too much, but also in terms of structural conditions of the teaching profession (Kelchtermans, 1993(Kelchtermans, , 2009)-being exposed and held accountable. Digitalisation has added further layers of complexity to teaching and learning (Mishra & Koehler, 2006;Orlando, 2013;Selwyn, Nemorin, Bulfin, & Johnson, 2017) in that it changes the circumstances and processes of teaching and learning as well as the roles, expectations, power, and values in educational contexts (Fransson, 2016). Although digital technologies can contribute added pedagogical value (George & Sanders, 2017;Haelermans, 2017), teachers may lack systematic strategies supporting students (Blikstad-Balas & Davies, 2017; and technologies may also result in teachers feeling pressurised to use them, even though this may be at odds with their own knowledge, practical skills, emotions, doubts about their potential, or their preferred ways of teaching (Convery, 2009;Howard, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, it was often observed that the so-called 'serious' devices (for learning) were often used to 'work around' teacher directives and enable students to game, socialize and listen to music which might constitute off-task behavior (see also Wiklund and Andersson, 2018). As detailed elsewhere (Selwyn et al, 2018;Selwyn et al, 2017), there are many crucial aspects for consideration in the schoolwide development and implementation of digital device policy and practices and their deployment in the bid to enhance learning and teaching.…”
Section: Resultsmentioning
confidence: 99%
“…It also explores teachers' understandings of the usefulness of these smartphones and of digital devices in general. In other publications, we have analysed and contrasted the different 'Bring Your Own Device' (BYOD) and information and communication technology policies of the school (Selwyn, Nemorin, Bulfin and Johnson, 2018;Selwyn, Nemorin, Bulfin and Johnson, 2017;Bulfin, Johnson, Nemorin and Selwyn, 2016). In this research project, three secondary schools were included in the study.…”
mentioning
confidence: 99%
“…Esses recursos não possibilitaram apenas o fortalecimento de indústrias, mas também o desenvolvimento de novas abordagens educacionais, como o E-Learning, os MOOCs e a utilização de muitas plataformas digitais (Pathak, 2016). Neste sentido, pesquisas buscam compreender o uso da tecnologia da informação em universidades, avaliando o uso de eletrônicos em sala de aula (Gökçearslan, Uluyol, & Şahin, 2018), as mudanças no cenário educacional devido às tecnologias (Selwyn, Nemorin, Bulfin, & Johnson, 2017), e o crescente uso de tecnologias móveis para ensino (Felisoni & Godoi, 2018) e etc.…”
Section: Influência Da Tecnologia Da Informação Em Modelos De Negóciounclassified